Intravenous sodium fluorescein enhances the visibility of vitreous during vitrectomy surgery for diabetic retinopathy - Siqueira,Rubens Camargo (2008)
OBJECTIVE: To observe the effectiveness of intravenous sodium fluorescein visibility in the vitreous during vitrectomy surgery in patients with diabetic retinopathy. METHODS: Fourteen consecutive cases of vitreoretinal surgery for vitreous hemorrhage and tractional retinal detachment secondary to diabetic retinopathy underwent intravenous injection of sodium fluorescein to 20% 1 hour before the surgery. The images of the steps of the surgeries were recorded. RESULTS: The sodium fluorescein stained green from the vitreous peripheral, vitreous base, posterior hyaloid, further improving visibility to a complete and more secure vitrectomy. The sodium fluorescein also stained fibrous points (sites of neovascularization) with high intensity making it easier its visibility. No complications associated with the dye injection were observed in all cases. CONCLUSION: Intravenous sodium fluorescein can be used safely for facilitating the observation of the vitreous, vitreous base, posterior hyaloid and sites of neovascularization. This technique can facilitate the process of vitrectomy in patients with diabetic retinopathy.